Design of a transducer-based amplifier system similar to an electronic stethoscope - Lim, Ivan Shi Cheng (Nanyang Technological University, 2022)
An electronic stethoscope is used to listen to the sound in a human body such as the heart or lungs. In this project, the electronic stethoscope is powered by a 2 AA battery. The electronic stethoscope consists of a microphone, pre-amplification circuit, filter circuit, power amplifier circuit as well as a LED comparator circuit. When the electret, condenser microphone is being biased by the battery, the output impedance is 2,200 ohms. The condenser microphone picks up the input signal, which is the heartbeat. It is then fed to the pre-amplifier circuit as the heartbeat is too small to be seen in the oscilloscope. The pre-amplifier circuit helps to amplify the heartbeat. However, it also amplified the environmental noise which is then filtered off by the filter circuit. This filtered signal is amplified by a variable volume control circuit to drive a speaker that is audible to the user. The electronic stethoscope also has a visual effect as it uses light emitting diodes to output the magnitude of the input signal after amplification.